Design and Development of tool for assessing OpenStreetMap Completeness - Arora, Sonali; Singh Sehra, Sukhjit; Kaur Sehra, Sumeet (International Journal of Computer Sciences and Engineering, 2025)
OpenStreetMap (OSM) is a cumulative effort to create a free presentable map of the world that can be accessed by anyone. OSM is one the most prevalent instance of Volunteered Geographic Information (VGI). Since OSM is generating large amount of spatial data that has been contributed by users with the different level of mapping experiences and different backgrounds, hence the quality of OSM data can vary strongly. For this different studies have been done in which different aspects have been investigated. In most of the studies, ground truth reference datasets have been used for comparison of the data which is called the extrinsic analysis. But extrinsic analysis is not always possible because of lack of availability of ground truth reference datasets. Hence, intrinsic analysis can serve as prominent basis for making the approximate statements on the quality of OSM. The investigation analyses the existing intrinsic frameworks and its limitations and then proposed the new six quality parameters for assessing the completeness of the OSM data effectively. A framework has been developed on the basis of proposed parameters. The results obtained from execution helps in doing the statistical analysis and interpretation by providing the visualizations in the form of bar charts, graphs, tables and maps to assess the completeness of data without the help of any ground truth reference datasets. This enables arbitrarily OSM completeness assessment for any part of the world.